Skin symptoms among workers in a spice factory - Meding, B (Contact dermatitis, 1993)
Workers in a Swedish spice factory (n = 70), and in the office (n = 23) of the same company, were investigated by questionnaire regarding skin symptoms. In a 2nd part of the study, subjects reporting skin symptoms were examined and investigated by patch and prick testing. Skin symptoms were reported by 1/2 the factory workers. Pruritus and skin irritation, particularly from cinnamon powder, were common. Patch test reactions to cinnamic aldehyde were found in 11/25 factory workers, but in several cases, the nature of the reactions was difficult to evaluate. Irritant patch test reactions were seen from powders of cardamom, paprika and white pepper. On prick testing, 6/25 workers reacted to cinnamic aldehyde. The results illustrate the difficulties of patch testing with spices and indicate the need for further research and validation of methods.